Structure of the bacterial cell division determinant GpsB and its interaction with penicillin‐binding proteins. Issue 5 (18th December 2015) - Rismondo, Jeanine; Cleverley, Robert M.; Lane, Harriet V.; Großhennig, Stephanie; Steglich, Anne; Möller, Lars; Mannala, Gopala Krishna; Hain, Torsten; Lewis, Richard J.; Halbedel, Sven
Summary: Each bacterium has to co‐ordinate its growth with division to ensure genetic stability of the population. Consequently, cell division and growth are tightly regulated phenomena, albeit different bacteria utilise one of several alternative regulatory mechanisms to maintain control. Here we consider GpsB, which is linked to cell growth and division in Gram‐positive bacteria. Δ gpsB mutants of the human pathogen Listeria monocytogenes show severe lysis, division and growth defects due to distortions of cell wall biosynthesis. Consistent with this premise, GpsB interacts both in vitro and in vivo with the major bi‐functional penicillin‐binding protein. We solved the crystal structure of GpsB and the interaction interfaces in both proteins are identified and validated. The inactivation of gpsB results in strongly attenuated virulence in animal experiments, comparable in degree to classical listerial virulence factor mutants. Therefore, GpsB is essential for in vitro and in vivo growth of a highly virulent food‐borne pathogen, suggesting that GpsB could be a target for the future design of novel antibacterials. Abstract : GpsB is a cell division protein and conserved in many Gram‐positive bacteria. Here we describe its function in growth, cell division and cell wall biosynthesis of the important human pathogen Listeria monocytogenes . Analysis of the three‐dimensional structure of GpsB now explains how GpsB binds to its interaction partner, the major bi‐functional penicillin binding protein PBP A1.